Titik Singgung Islam dan Kepercayaan Tradisi dalam Sĕrat Dahor Palak - Fajar Wijanarko (Manuskripta, 2018)
Islam Java is being an accommodation between Islam Santri and the traditional faith of Javanese. Geertz stands for these condition with classifying typologies of Javanese community which consists of abangan, santri and priyayi. The classification of Javanese communities is affected by literature produced in the beginning of 17th century, such as Sĕrat Dahor Palak. On the text of Dahor Palak, the emergence of element syncretism seen from selection diction used to figure Allah as the lord of. The story of prophets recorded in the text and illumination with Arabic alphabet on the manuscript are strengthened Islamic image. Philology approach by exposure to descriptive be a proved the point of tangency between Islam and the traditional faith of Javanese community in the text. In the end, this articles provides a syncretism in the Islamic literature produced in the 17th century from language aspect. --- Islam Jawa menjadi bentuk akomodasi antara ‘Islam Santri’ dengan sistem kepercayaan masyarakat Jawa. Geertz mengamini kondisi demikian dengan mengklasifikasi tipologi masyarakat Jawa yang terdiri atas abangan, santri, dan priyayi. Pola masyarakat Jawa tersebut selanjutnya mempengaruhi pula produksi karya sastra di awal abad XVII, salah satunya Sĕrat Dahor Palak. Pada teks Dahor Palak, munculnya unsur sinkretis terlihat dari pemilihan diksi yang digunakan untuk melukiskan Allah sebagai sang pencipta. Cerita para nabi yang direkam dalam teks serta iluminasi beraksara Arab pada lembaran-lembaran naskah Dahor Palak turut memperkuat citra Islam. Pendekatan filologi dengan pemaparan deskriptif menjadi upaya membuktikan titik singgung antara Islam dengan sistem kepercayaan tradisi dalam teks Dahor Palak. Pada akhirnya, artikel ini memberi gambaran tentang sikretisme dalam produksi sastra Islam abad ke XVII yang dibentuk dari aspek kebahasaannya.